2015
DOI: 10.1016/j.toxlet.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Lung distribution, quantification, co-localization and speciation of silver nanoparticles after lung exposure in mice

Abstract: Large knowledge gaps still exist on the toxicological mechanisms of silver (Ag) engineered nanoparticles (ENPs); a comprehensive understanding of the sources, biodistribution, toxicity and transformation of Ag ENPs along their life cycle and after transfer in living organisms is needed. In a previous study, mice were pulmonary exposed to Ag ENPs and local (lung) and systemic toxic effects together with biodistribution to organs including heart, liver, spleen and kidney were investigated. Here, Ag lung distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 37 publications
(43 reference statements)
2
26
0
Order By: Relevance
“…Similar results were obtained also by Jiang and collaborators on Chinese hamster ovary cells [60]. A further confirmation of macrophage role in AgNPs clearance and toxicity was made by Smulders and collaborators [61]. Compared to other works, the authors provided the Ag lung biodistribution and speciation in vivo of different size NPs by means of XRF, XANES, and PIXE techniques combined approach.…”
Section: Speciation Of Metallic Nanoparticlessupporting
confidence: 69%
See 1 more Smart Citation
“…Similar results were obtained also by Jiang and collaborators on Chinese hamster ovary cells [60]. A further confirmation of macrophage role in AgNPs clearance and toxicity was made by Smulders and collaborators [61]. Compared to other works, the authors provided the Ag lung biodistribution and speciation in vivo of different size NPs by means of XRF, XANES, and PIXE techniques combined approach.…”
Section: Speciation Of Metallic Nanoparticlessupporting
confidence: 69%
“…The most important data however, came from SXRF analysis and histology comparison: first, a local macrophage increase in the lungs was observed. Second, Ag NPs presence was shown in approximately a quarter of all macrophages in the lumen [61].…”
Section: Speciation Of Metallic Nanoparticlesmentioning
confidence: 98%
“…Rather, ROS production following minimal cellular insult induces mast cell activation. Silver NPs can either damage cell membranes or enter cells by diffusion for some cell types, including endothelial cells or hepatocytes, and by endocytosis in phagocytic cells . The K + efflux followed by membrane damage may trigger histamine release from mast cells directly or indirectly via the production of intracellular ROS .…”
Section: Resultsmentioning
confidence: 99%
“…This may result from slowed pulmonary clearance of particles administered by instillation compared to inhalation [45] or the dissolution and formulation of other NP or salt participates [24,36,46] The contribution of silver ions to the observed toxicity observed remains a possible mechanism. It has been reported that 20 nm citrate capped AgNP quickly dissolutes in water however, this dissolution can be slowed in the presence of dipalmitoylphosphatidylcholine a componenet of surfactant [23,47].…”
Section: Discussionmentioning
confidence: 99%